Obstetric and intensive-care strategies in a high-risk pregnancy with critical respiratory failure due to COVID-19: A case report - Zuzana Kolkova; Martin F. Bjurström; John-Kalle Länsberg; Eimantas Svedas; Maria Andrada Hamer; Stefan R. Hansson; Andreas Herbst; Mehreen Zaigham (Elsevier, 2020)
Background: With the disease burden increasing daily, there is a lack of evidence regarding the impact of COVID-19 in pregnancy. Healthy pregnant women are still not regarded as a susceptible group despite physiological changes that make pregnant women more vulnerable to severe infection. However, high-risk pregnancies may be associated with severe COVID-19 disease with respiratory failure, as outlined in this report. We discuss the importance of timely delivery and antenatal steroid administration in a critically ill patient. Case: A 27-year-old pregnant woman (gravida 2, para 1) with type I diabetes, morbid obesity, hypothyroidism and a previous Caesarean section presented with critical respiratory failure secondary to COVID-19 at 32 weeks of gestation. A preterm emergency Caesarean section was performed, after steroid treatment for foetal lung maturation. The patient benefited from prone positioning; however, transient acute renal injury, rhabdomyolysis and sepsis led to prolonged intensive care and mechanical ventilation for 30 days. The baby had an uncomplicated recovery. Conclusion: COVID-19 infection in high-risk pregnancies may result in severe maternal and neonatal outcomes such as critical respiratory failure requiring mechanical ventilation and premature termination of the pregnancy. Antenatal steroids may be of benefit for foetal lung maturation but should not delay delivery in severe cases.